Mucin Muc2 Deficiency and Weaning Influences the Expression of the Innate Defense Genes Reg3β, Reg3γ and Angiogenin-4 - Burger-van Paassen, Nanda; Loonen, Linda M. P.; Witte-Bouma, Janneke; Korteland-van Male, Anita M.; de Bruijn, Adrianus C. J. M.; van der Sluis, Maria; Lu, Peng; Van Goudoever, Johannes B.; Wells, Jerry M.; Dekker, Jan; Van Seuningen, Isabelle; Renes, Ingrid B. (PLOS ONE, 2012)
Background Mucin Muc2 is the structural component of the intestinal mucus layer. Absence of Muc2 leads to loss of this layer allowing direct bacterial-epithelial interactions. We hypothesized that absence of the mucus layer leads to increased expression of innate defense peptides. Specifically, we aimed to study the consequence of Muc2 deficiency (Muc2−/−) on the expression of regenerating islet-derived protein 3 beta (Reg3β), regenerating islet-derived protein 3 gamma (Reg3γ), and angiogenin-4 (Ang4) in the intestine shortly before and after weaning. Methods Intestinal tissues of Muc2−/− and wild-type (WT) mice were collected at postnatal day 14 (P14, i.e. pre-weaning) and P28 (i.e. post-weaning). Reg3β, Reg3γ, and Ang4 expression was studied by quantitative real-time PCR, Western-blot, in situ hybridization, and immunohistochemistry. Results Reg3β and Reg3γ were expressed by diverging epithelial cell types; namely enterocytes, Paneth cells, and goblet cells. Additionally, Ang4 expression was confined to Paneth cells and goblet cells. Expression of Reg3β, Reg3γ, and Ang4 differed between WT and Muc2−/− mice before and after weaning. Interestingly, absence of Muc2 strongly increased Reg3β and Reg3γ expression in the small intestine and colon. Finally, morphological signs of colitis were only observed in the distal colon of Muc2−/− mice at P28, where and when expression levels of Reg3β, Reg3γ, and Ang4 were the lowest. Conclusions Expression of Reg3 proteins and Ang4 by goblet cells point to an important role for goblet cells in innate defense. Absence of Muc2 results in up-regulation of Reg3β and Reg3γ expression, suggesting altered bacterial-epithelial signaling and an innate defense response in Muc2−/− mice. The inverse correlation between colitis development and Reg3β, Reg3γ, and Ang4 expression levels might point toward a role for these innate defense peptides in regulating intestinal inflammation.